2020
DOI: 10.1097/mpa.0000000000001597
|View full text |Cite
|
Sign up to set email alerts
|

The North American Neuroendocrine Tumor Society Consensus Guidelines for Surveillance and Medical Management of Pancreatic Neuroendocrine Tumors

Abstract: This article is the result of the North American Neuroendocrine Tumor Society consensus conference on the medical management of pancreatic neuroendocrine tumors from July 19 to 20, 2018. The guidelines panel consisted of medical oncologists, pathologists, gastroenterologists, endocrinologists, and radiologists. The panel reviewed a series of questions regarding the medical management of patients with pancreatic neuroendocrine tumors as well as questions regarding surveillance after resection. The available lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
108
0
15

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(141 citation statements)
references
References 193 publications
2
108
0
15
Order By: Relevance
“…The percentage of Ki-67 nuclear staining (Ki-67 index; Fig. S1C-F) (13) was used to determine the grade of PNET (14). The histological diagnosis of tumors was performed and confirmed by two pathologists.…”
Section: Methodsmentioning
confidence: 99%
“…The percentage of Ki-67 nuclear staining (Ki-67 index; Fig. S1C-F) (13) was used to determine the grade of PNET (14). The histological diagnosis of tumors was performed and confirmed by two pathologists.…”
Section: Methodsmentioning
confidence: 99%
“…Others have shown that resection of duodenal gastrinomas, regardless of symptoms, prolongs survival. 36,37 In our patient, given the pNET size and absence of a clinical syndrome, we decided to proceed with active surveillance.…”
Section: Duodenopancreatic Netmentioning
confidence: 99%
“…FIGURE 4. Framework for Initial Management and Surveillance of the Patient With Multiple Endocrine Neoplasia Type 1 (MEN1) 1,10,11,15,32,36,65. (A) General flowchart, (B) parathyroid gland management, (C) duodenopancreatic neuroendocrine tumor (dpNET) management, and (D) pituitary adenoma (PA) management are illustrated.…”
mentioning
confidence: 99%
“…Several new therapies have been approved to treat well-differentiated advanced gastroentero-pancreatic neuroendocrine neoplasms (GEP-NENs) in the last twenty years [1]. European Neuro-Endocrine Tumor Society (ENETS) and North American Neuro-Endocrine Tumor Society (NANETS) guidelines [2][3][4] recommend somatostatin analogs (SSAs) alone as first-line therapy. Interferon-α, tyrosine kinase inhibitors (Everolimus and Sunitinib), or peptide receptor radionuclide therapies (PRRT) are considered only in patients with progressive diseases as a second or further line of treatment.…”
Section: Introductionmentioning
confidence: 99%